2020
DOI: 10.3390/ijerph17197207
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Risk Perception of Cell Phones and Objective Knowledge of EMF in Korea

Abstract: This study examines differences between the level of objective knowledge regarding radio-frequency electromagnetic fields (RF-EMF) and risk perception of cell phones in Korea. We also investigate the extent to which socio-demographic factors, perceived EMF exposure, objective knowledge regarding EMF, and psychological factors influence the risk perception of cell phones using hierarchical multiple regression. All 3393 study subjects completed a survey measuring the degree of risk perception of EMF. They were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, this study did not find a significant relationship between knowledge level and risk perception. Furthermore, Seo’s research showed that the mastery of magnetic field knowledge affects Koreans’ cognition of the harm of mobile phones [ 52 ]. It is also inconsistent with the results of the research on mine-related heat exposure risk cognition; that is, miners’ cognition is affected by their work experience and knowledge level [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not find a significant relationship between knowledge level and risk perception. Furthermore, Seo’s research showed that the mastery of magnetic field knowledge affects Koreans’ cognition of the harm of mobile phones [ 52 ]. It is also inconsistent with the results of the research on mine-related heat exposure risk cognition; that is, miners’ cognition is affected by their work experience and knowledge level [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the 95% confidence interval for the total exposure ratio ( 2.5% ), 97.5% is calculated as: 2.5% = − U ( ) and 97.5% = + U ( ) (12) In order to declare that an exposure level as measured complies with the Greek safety limits imposed in Greek VOLUME 11, 2023 legislation, the Greek Atomic Energy Commission demands the measured values in addition to the expanded uncertainty to be below the reference values, so for the final decision we use the interval according to 12.…”
Section: ) Statistical Uncertainty Type Bmentioning
confidence: 99%
“…Due to these developments, in recent years, people have become increasingly concerned about potential health hazards posed by wireless and especially mobile networks [12]. The proximity of base stations to populated areas is of particular concern, as it has been claimed to pose particular health risks to the population.…”
Section: Introductionmentioning
confidence: 99%